Limits of Flow-Cytometry Histogram Analysis Methods to Assess Bladder Tumour Antigen Expression - Chabanas, Agnès (Anal Cell Pathol, 1997)
Tumour‐associated antigens detected in cells obtained from bladder washings or tumours are useful markers in bladder cancer. Flow cytometry is commonly used to quantify immuno‐stained cells. A straightforward way to analyze data is to count the fluorescent cells above a threshold empirically determined on a control histogram representation. However, specific antigens expressed at highly variable rates give rise to wide range distributions in flow cytometry as illustrated when a mucin antigen for urinary bladder was titrated by M344 monoclonal antibody in urothelial cancer cells. We have evaluated several methods of background estimation and subtraction in order to determine the proportion of M344 Mab positive cells. These include threshold setting (Histogram Shape Dependent (HSD) threshold developped in this study, 2% preset or 5% preset background), subtraction of the blank from the test histograms, and Kolmogorov–Smirnov statistical test. The HSD method appeared to be a more reliable method for background estimation; however, in the case of very low antigen expression, where specific fluorescence histograms could hardly be distinguished from that of the background, fluorescence microscopy remained the only valid method, since it allowed the distinction between specific and non‐specific fluorescence on the basis of structural differences between the two.